Ficus carica extract impregnated amphiphilic polymer scaffold for diabetic wound tissue regenerations. Issue 1 (1st January 2021) - Feng, Jia; Niu, Yu; Zhang, Yi; Zuo, Hong; Wang, Shujin; Liu, Xufeng
Abstract: Diabetes associated injury healing and other tissue irregularities are viewed as a significant concern. The purpose of the study is to design the wound regeneration activity of Ficus carica extract (FFE) loaded amphiphilic polymeric scaffold of poly(xylitol- g -adipate- co -glutamide) (PXAG)–polyhydroxybutyrate (PHB) for potential diabetic affected wound regeneration. The PXAG copolymer was prepared by the condensation method, and the polymeric scaffolds of PXAG-PHB, PXAG-PHB/FFE were developed through the ultra-sonication process and magnetic stirrer processes. The chemical structure, crystalline nature, thermal stability, size, surface charge and surface morphology of PXAG-PHB and PXAG-PHB/FFE polymeric scaffolds were investigated. The PXAG-PHB/FFE exhibits 99.0% free radical scavenging activity which was determined by the DPPH method. The inhibition zones by the PXAG-PHB/FFE indicate it had a higher antibacterial activity with the Escherichia coli (gram-negative) and Staphylococcus aureus (gram-positive) pathogens. The PXAG, PXAG-PHB and PXAG-PHB/FFE polymeric scaffolds exhibited good viability against diabetic induced wound cells (WS1) in 100 μg/mL concentrations up to 72 h incubation. Since the synthesized PXAG-PHB/FFE polymeric scaffolds possess excellent thermal stability, bioactivity, biocompatibility and antioxidant activity along with potent antimicrobial activity, they play a potential role in diabetic wound tissue regenerations.